Sequence Variability and Functional Analysis of Robo2 Genes in Three Nigerian Indigenous Chicken Strains - Yeigba, Japhet Bolouinbele; Sweet-Owei, Inara Favour; Tari, Blessing Oyeinbomoere (Faculty of Natural and Applied Sciences Journal of Computing and Applications, 2025)
This study investigated the sequence variability and functional implications of ROBO2 genes (Roundabout Guidance Homolog gene 2), across three strains of Nigerian indigenous chickens: normal feathered, naked Neck, and frizzle feather, were used in the experiment. Nucleotide sequences were retrieved from the National Centre for Biotechnology Information (NCBI) database and subjected to multiple sequence alignment using the COBALT tool. The aligned sequences were then analysed for variability using the MEGA X suite. Conserved regions within the sequences were determined, and phylogenetic relatedness was assessed using Conservation and BLOSUM80 settings. The study provides insights into the genetic diversity and evolutionary relationships of ROBO2 genes among different strains of Nigerian indigenous chickens, shedding light on potential functional implications and genetic conservation efforts in poultry breeding programs. Despite the considerable variability in amino acid sequences, subsequent alignment analysis revealed a high level as well as degree of conservation at the protein level. Using conclusion a clearer understanding of the sequence variability, further analysis using the MEGA X suite was conducted, resulting in a patterned table that highlighted the presence of INDELs and mutations contributing to the observed diversity. This unexpected finding suggests that while the sequences may differ in their constituent amino acids, the overall structure and function of the ROBO2 protein remain highly conserved across species. Therefore, it is recommended that exploration of genotype-phenotype relationships, investigation of genetic variants contributing to environmental adaptability, and consideration of epigenetic modulation in phenotype expression. This multidisciplinary approach aims to enhance understanding of the genetic diversity and adaptive potential of indigenous Nigerian chicken populations.